The renal-bone axis in older people living with HIV on stable antiretroviral therapy: A sub-analysis of the GS-US-104-0423 study. Issue 4 (24th August 2022) - Alvarez, Elena; Campbell, Lucy; Tinago, Willard; Garcia-Leon, Alejandro; Walsh, Ian; Brady, Jennifer J; Burling, Keith; Noe, Sebastian; Neuville, Marie F; Jouret, Francois; Jamshidian, Farid; Graham, Hiba; et al.
Background: Data on low bone mineral density (BMD) in people living with HIV (PLWH) are mainly derived from younger adults; little is known about how antiretroviral therapy (ART) and alterations in the renal-bone axis relate to BMD in older PLWH. Methods: Cross-sectional study of men > 50 years and post-menopausal women with HIV. Antiretroviral therapy exposure was stratified into four groups based on use of tenofovir disoproxil fumarate (TDF) and protease inhibitors (PI): non-TDF/non-PI, non-TDF/PI, TDF/non-PI, and TDF/PI. Bone mineral density was measured by dual X-ray absorptiometry (DXA). Bone turnover/regulatory markers and renal tubular function were analysed in stored plasma and urine samples. The association of ART exposure and bone/renal biomarkers on BMD was explored using logistic regression models. Results: 247 individuals (median [IQR] age 57 [53, 65] years; 47% female; 13% of Black ethnicity; CD4 count 643 [473, 811] cells/mm 3 ; and 98% with HIV RNA < 200 copies/mL) were included. Bone turnover and renal tubular function differed significantly by ART exposure. In analyses adjusted for demographic and traditional renal/bone risk factors, exposure to TDF and PI was associated with a fourfold greater risk of low BMD at the femoral neck and exposure to TDF and/or PI with a threefold greater risk of low BMD at the lumbar spine. The relationship between ART and low BMD was not altered by further adjustment for bone turnover or renal tubular function markers. Conclusions: The associations between low BMD and ART exposure (TDF vs. non-TDF and boosted vs. unboosted third agents) were minimally affected by adjustments for bone and kidney biomarkers.